Intra-procedural and delayed bleeding after resection of large colorectal lesions: The SCALP study. Issue 10 (December 2019) - Amato, Arnaldo; Radaelli, Franco; Correale, Loredana; Di Giulio, Emilio; Buda, Andrea; Cennamo, Vincenzo; Fuccio, Lorenzo; Devani, Massimo; Tarantino, Ottaviano; Fiori, Giancarla; De Nucci, Germana; De Bellis, Mario; et al.
Background and aim: The safety of endoscopic resection of large colorectal lesions (LCLs) (≥20 mm) is clinically relevant. The aim of the present study was to assess the rate of post-resection adverse events (AEs) in a real-life setting. Patients and methods: In a prospective, multicentre, observational study, data from consecutive resections of LCLs over a 6-month period were collected in 24 centres. Patients were followed up at 15 days from resection for AEs. The primary endpoint was intra-procedural bleeding according to lesion morphology. Secondary endpoints were delayed bleeding and perforation. Patient and polyp characteristics, and polypectomy techniques were analysed with respect to the bleeding events. Results: In total, 1504 patients (female/male: 633/871, mean age, 66.1) with 1648 LCLs (29.1% pedunculated and 70.9% non-pedunculated lesions) were included. Overall, 168 (11.2%) patients had post-resection bleeding (8.5 and 2.0% immediate and delayed, respectively), while 15 (1.0%) cases of perforation occurred. Independent predictors of immediate bleeding for pedunculated lesions were bleeding prophylaxis (odds ratio (OR) 0.28, 95% confidence interval (CI) 0.13–0.62), simple polypectomy (versus endoscopic mucosal resection, OR 0.38, 95% CI 0.17–0.88) and inpatient setting (OR 2.21, 95% CI 1.07–5.08), while bleeding prophylaxis (OR 0.37, 95% CI 0.30–0.98), academic setting (OR 0.27, 95% CI 0.12–0.54) and size (OR 1.03, 95% CI 1.00–1.05) were predictors for those non-pedunculated. Indication for colonoscopy (screening versus diagnostic (OR 0.33, 95% CI 0.12–0.86)), antithrombotic therapy (OR 3.12, 95% CI 1.54–6.39) and size (OR 2.34, 95% CI 1.12–4.87) independently predicted delayed bleeding. Conclusions: A low rate of post-resection AEs was observed in a real-life setting, reassuring as to the safety of endoscopic resection of ≥2 cm colorectal lesions. Bleeding prophylaxis reduced the intra-procedural bleeding risk, while antithrombotic therapy increased delayed bleeding. CLINICALTRIAL: (NCT02694120).